Public Perception of Ménière's Disease: A Social Media Analysis. Issue 2 (21st February 2023) - Hamdi, Osama A.; Bellinger, Jeffrey R.; Wright, Garrison P.; Churnin, Ian T.; Strumpf, Andrew M.; Casazza, Geoffrey C.; Kesser, Bradley W.
Abstract : Objective: To analyze tweets associated with Ménière's disease (MD), including type of users who engage, change in usage patterns, and temporal associations, and to compare the perceptions of the general public with healthcare providers. Methods: An R-program code, academictwitterR API, was used to query Twitter. All tweets mentioning MD from 2007 to 2021 were retrieved and analyzed. Valence Aware Dictionary and Sentiment Reasoning was used as a model to assess sentiment of tweets. Two reviewers assessed 1, 007 tweets for qualitative analysis, identifying the source and the topic of the tweet. Results: A total of 37, 402 tweets were analyzed. The number of tweets per user ranged from 1 to 563 (M = 33.7, SD = 91.1). Quantitative analysis showed no temporal or seasonal association; however, tweeting increased when celebrities were diagnosed with MD. Of the 1007 representative tweets analyzed, 60.6% of tweets came from the general public and were largely of negative sentiment focusing on quality of life and support, whereas healthcare providers accounted for 23% of all tweets and focused on treatment/prevention. Tweets by news sources accounted for the remaining 13% of all tweets and were primarily positive in sentiment and focused on awareness. Conclusions: MD is commonly tweeted about by the general public, with limited input regarding the disease from healthcare providers. Healthcare providers must provide accurate information and awareness regarding MD, especially when awareness is highest, such as when celebrities are diagnosed. Level of Evidence: Level IV. Indicate IRB or IACUC Not applicable.